Emulsomes: A Promising Tool for Lipophilic Drug Delivery - Dipti Gohil; Nirmal Shah; Sunil Kardani; Kinjal Patel; Shivkant Patel; Rajesh A. Maheshwari; Piyush Sadhu; Mamta Kumari; Niyati Shah (Pharmaceutical Research - Recent Advances and Trends Vol. 3, 2024)
Emulsomes, which are lipid-based nanocarriers, combine the advantages of liposomes and emulsions, providing a versatile platform for the encapsulation and controlled release of hydrophobic drugs. This chapter provides a comprehensive overview of the structural characteristics, preparation methods, and functional properties of emulsomes, highlighting their role in overcoming the challenges associated with the delivery of poorly water-soluble drugs. Key topics include the physicochemical properties of emulsomes, such as their size, stability, and drug-loading capacity, which are crucial for their effectiveness in drug delivery. The chapter details various preparation techniques, including high-pressure homogenization and solvent evaporation methods, and discusses how these techniques influence the characteristics and performance of emulsomes. The potential applications of emulsomes in improving the bioavailability and therapeutic efficacy of lipophilic drugs are thoroughly examined. Case studies and experimental data are presented to illustrate the successful use of emulsomes in delivering anticancer agents, antifungal drugs, and other therapeutic compounds. Additionally, the chapter delves into the mechanisms of drug release from emulsomes and the factors that affect their in vivo behavior, such as particle size and surface modifications. Safety, biocompatibility, and regulatory considerations are also addressed, emphasizing the importance of thorough preclinical and clinical evaluations to ensure the safe use of emulsomes in medical applications. Finally, the chapter discusses future directions in emulsome research, including the development of multifunctional emulsomes and their potential use in personalized medicine.